2019
DOI: 10.1186/s13048-019-0547-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the addition of Early Embryo Viability Assessment to morphological evaluation on the accuracy of embryo selection on day 3 or day 5: a retrospective analysis

Abstract: In this study we aimed at retrospectively assessing in a homogeneous group of IVF patients whether the addition of Early Embryo Viability Assessment (Eeva™) to standard morphology increases the accuracy of embryo selection in case of double embryo transfer (DET) on day 3 or single embryo transfer (SET) on day 5. Eeva™ is an algorhythm aimed at indicating on day 3, according to morphokinetic parameters observed in the first three days of embryo growth, which embryos are more likely to develop into viable blasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…It results in a higher implantation rate, and increases clinical pregnancy rates. 15 This was in line with other studies which found that extending embryo culture to day 5 can be a better strategy for identifying and selecting groups of embryos with a higher overall probability of success for implantation. 16 Embryo implantation is a complex process.…”
Section: Resultssupporting
confidence: 88%
“…It results in a higher implantation rate, and increases clinical pregnancy rates. 15 This was in line with other studies which found that extending embryo culture to day 5 can be a better strategy for identifying and selecting groups of embryos with a higher overall probability of success for implantation. 16 Embryo implantation is a complex process.…”
Section: Resultssupporting
confidence: 88%
“…Forty-five studies [ 2 , 11 , 13 , 15 , 21 , 24 , 28 31 , 38 , 39 , 43 , 44 , 48 – 50 , 53 , 54 , 56 59 , 62 , 64 , 66 69 , 72 , 75 – 77 , 79 81 , 85 87 , 91 , 93 96 , 98 ] were pooled and found that the MPR was significantly lower in the SET group than in the DET group (0.05, 0.04–0.06, I 2 = 2%, P < 0.001) (Supplementary Fig. S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, embryo development was assessed using the TLS Geri plus ® [ 20 ], providing a continuous surveillance of embryo growth, while maintaining stable culture conditions. TLS was claimed to have the potential to improve embryo selection capability and, in turn, IVF outcome [ 56 ]; indeed, some studies reported higher pregnancy rates using this technology [ 57 ], whereas others did not confirm any advantage vs. standard morphological embryo selection protocols [ 58 , 59 , 60 ]. Overall, we observed similar embryo morphokinetic parameters between the two study groups, but a significantly higher proportion of embryos displaying an optimal cleavage range in the very early stages of embryo development (t2 and t3) was observed in the MI + ALA + FA group compared to the FA-only group, revealing a potential, although limited, positive impact on embryo kinetics.…”
Section: Discussionmentioning
confidence: 99%